Thyroid papillary cancer-related pregnancy: a case report - ESİM BÜYÜKBAYRAK, ESRA (WALTER DE GRUYTER GMBH, 2017)
Differentiated thyroid cancer is the second-most frequent tumor among those tumors diagnosed during pregnancy after breast cancer; it also is the most common endocrine malignancy. Pregnancy-associated cancer was defined as a malignancy detected during pregnancy or within 2 years of delivery, but most of the patients with pregnancy-associated cancer were recognized in the postpartum period. The best time for surgery is unclear. Its management is a challenge for both doctors and patients. Enlargement of the thyroid gland in pregnancy is usually a physiological change related to pregnancy, but even if it is rare, it can be due to thyroid malignancy. We report a case of 31-year-old female diagnosed with thyroid papillary cancer during pregnancy with no symptoms except for a lump on her neck. For this reason, the examination of the thyroid gland and the examination of neck lymph nodes should be routinely performed on all pregnant women.
Keywords: Iodine-131; pregnancy; thyroid cancer; MOLECULAR-FEATURES; WOMEN; PATIENT